HYGIENE AND HEALTH CONDITION OF CHILDREN FROM NETRAKONA BANGLADESH AMONG GARO AND NON GARO COMMUNITIES - I. Hussain, (Pakistan Journal of Science, 2022)
A survey was conducted to investigate the potential factors of food-hygiene practices of mothers on sanitation and health condition among children of Netrakona Bangladesh in Garo (tribal) and Non Garo communities. The food-hygiene practices included hand-washing, method of washing utensils, separation of utensils for raw and cooked food, and the location where foods were prepared for cooking. A face-to-face interview was conducted, and data on 270 household were analyzed. The risk of unhygienic system was significantly higher among children. The mothers of targeted area prepared food by cooking in unhygienic kitchen, improper hand washing and mothers preparing food for their children in common utensils. These results indicate that food-hygiene practices are more common in Garo community than Non Garo. This has a potential impact in preventing diarrhea/diseases among children of Non Garo community.